Muscle volume alterations in spastic muscles immediately following botulinum toxin Type-A treatment in children with cerebral palsy - Williams, Sian; Reid, S.; Elliott, Catherine; Shipman, P.; Valentine, J. (Wiley-Blackwell Publishing Ltd., 2013)
AIM: With evidence for an atrophic effect of botulinum toxin type A (BoNT-A) documented in typically developing muscles, this study investigated the immediate morphological alterations of muscles in children with cerebral palsy (CP) after BoNT-A treatment. METHOD: Fifteen children (10 males, five females; age range 5-11y, mean age 8y 5mo, SD 1y 10mo) with spastic diplegic CP [Gross Motor Function Classification System Levels I (n=9) and II (n=6)] receiving BoNT-A injections for spasticity management were included. None of the children was a first-time receiver of BoNT-A. Magnetic resonance imaging and Mimics software assessed muscle volume, timed 2 weeks before and 5 weeks after injection. All participants received BoNT-A bilaterally to the gastrocnemius muscle, and five participants also received BoNT-A bilaterally to the medial hamstring muscles. Functional assessment measures used were the 6-Minute Walk Test (6-MWT), the Timed Up and Go (TUG) test, and hand-held dynamometry. RESULTS: Whilst total muscle group volume of the injected muscle group remained unchanged, a 4.47% decrease in the injected gastrocnemius muscle volume (p=0.01) and a 3.96% increase in soleus muscle volume (p=0.02) was evident following BoNT-A. There were no statistically significant changes in function after BoNT-A as assessed by the TUG. There was also no statistically significant change in distance covered in the 6-MWT. Muscle strength, as assessed using hand-held dynamometry was also not statistically different after BoNT-A treatment.INTERPRETATION: Muscle volume decreases were observed in the injected muscle (gastrocnemius), with synergistic muscle hypertrophy that appeared to compensate for this decrement. The 4% to 5% decrease in the volume of BoNT-A injected muscles are not dramatic in comparison to reports in recent animal studies, and are a positive indication for BoNT-A, particularly as it also did not negatively alter function.